Publishers, curriculum developers and educational stakeholders in textbook development for building a virile educational foundation in Nigeria (2011)
The book is a medium of mass communication which influences effective utilisation of other media. It is a literary work, printed or written, which propels and enhances national development. The role of books in literary, educational, political and social development of any nation cannot be over emphasised in the sense that the degree of national development is determined by level of literacy which is aided by book publication. Book is a primary means of inculcating and transmitting knowledge. No educational development succeeds without effective utilisation of the book, since the book is the printed material or electronic material used in preserving knowledge for onward transmission. In the light of the above, it becomes imperative for both publishers and educational administrators to increase commitment in the development and selection of books meant for use in schools at all stages of education in order to properly realise the national education philosophy. This paper therefore assesses the efforts made by Nigerian government to actualise the country's education philosophy, the role of publishers as well as the methods of selecting books for adoption in schools.